Al-Mashlahah and Reinterpretation of Islamic Law in Contemporary Context - Zuhdi, Muhammad Harfin; Abdun Nasir, Mohamad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Substantially, all Islamic law comes with a mission of benefiting humans, as the theory of al-mashlahah suggests. This article elaborates extensively on the theory of al-mashlahah in the discourse of Islamic legal thought from classical to contemporary times, starting from al-Ghazâli's theory of al-mashlahah in his book al-Mustashfa to `Izz al-Dîn ibn 'Abd al-Salâm’s concept of jalb al-manafi wa daf’u al-mafasid (taking benefit, refuting harm) and al-Shatibi with a comprehensive integralistic approach in his work al-Muwafaqat. Contemporary Muslim intellectuals, such as Ibn Asyur, Abdul Majid Al-Najjar, Jamaluddin 'Athiyah and Jasser Auda further develop this theory. This article finds that there is a continuous dynamic of Islamic legal methods related to the theory of al-mashlahah, which is used as an argument in the contemporary era, transforming into maqashid al-shariah. The reform in Islamic law mostly makes use of the maqashid as the basic paradigm, which covers not only individual but also social, communal and universal social benefits. In this context, Al-Najar, 'Athiyyah, and Jasser Auda offer new scope and dimensions of maqasid al-shari'ah theory to answer the problems of contemporary Islamic law.